Karya Seni Rupa Mixed Media Tentang Persistence Melalui Inline Skating - Yunita, Popy Sinta; Ok-Jeon, Jeong (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
Inline Skate is a sport that is now gaining popularity again due to the Covid-19 pandemic. this artwork comes from personal experience with inline skates. has an affinity for inline skating, especially aggressive inline skating, and then uses the sport as a source of inspiration for works of art. Starting from remembering the pleasant experience of using roller skates as a child. For artist, inline skating is like therapy and self-discovery so that it makes mentally better and more confident. and persistence in pursuing inline skating made several changes in oneself starting from mental, physical and other achievements. The artist's interest in artistic creations is reflective (a reflection of personal experience), and the form shown is semi-figurative. The method of creating works of art uses Artistic Research (exercise and creation are done together). This work is mixed media art. The artist hopes that this work can provide motivation and positive emotional impressions such as joy, curiosity, fatigue, ambition, high adrenaline, pain and feelings of falling when pursuing Inline Skating.